Indonesia Model Pengelolaan Zakat Untuk Pemberdayaan Ekonomi Mustahik di Baznas Kota Padang pada Masa Pandemi: Model Pengelolaan Zakat Untuk Pemberdayaan Ekonomi Mustahik di Baznas Kota Padang pada Masa Pandemi - Basri, Darmawati, Yondra, Epen, Didi, Riza, Yuki, Reo Rahmanza (AL-UKHWAH - JURNAL PENGEMBANGAN MASYARAKAT ISLAM, 2022)
This research is motivated by effort empowerment community done by Baznas City Field through. The program for the distribution and utilization of zakat funds through the economic sector made wrong one form utilization consumptive and productive zakat. On time baznas pandemic City Padang received several awards. Baznas has also provided assistance to mustahik, either in the form of basic necessities or in the form of business tools. Based on these facts, it is important for researchers to conduct research on zakat management models for economic empowerment of mustahik in the Padang City Baznas during the pandemic. The formulation of the problem in this study is: What is the Zakat Management Model for Mustahik Economic Empowerment at the Padang City Baznas During the Pandemic Period?. Limitations of the problems in this study: 1) Consumptive Zakat Management Model for Mustahik Economic Empowerment at the Padang City Baznas during a Pandemic, 2) Productive Zakat Management Model for Mustahik Economic Empowerment in Padang City Baznas during a Pandemic. The purposes of this study are 1) To determine the model of consumptive Zakat management for Mustahik Economic Empowerment in the Padang City Baznas during the Pandemic Period. 2). To find out the productive zakat management model for economic empowerment of mustahik in the Padang City Baznas during the pandemic. The method used in this research is field research and uses a qualitative approach. Informants in this study consisted of the Chairperson of the Padang City Baznas, Padang City Baznas staff and Mustahik Padang City Baznas. Data collection techniques are by means of observation, documentation and interviews. The process of analyzing the data is done through data reduction, data display and drawing conclusions. The results showed that: 1).Consumptive zakat is there by giving or distributing zakat funds to mustahik in the form of rice in the first stage, while entering the second stage coincides with the month of Ramadan Baznas provides assistance in the form of basic necessities. Baznas also provides consumptive assistance in the form of scholarships to elementary and junior high school students.2).Productive zakat is by providing business equipment assistance to mustahik who have special expertise in their respective fields.Baznas also provides additional capital assistance for mustahik who want to become entrepreneurs while there is no capital or even to continue their business. Keywords :Management, Zakat, Empowerment